Motivation and involvement in adventure tourism activities: a Chinese tourists' perspective. Issue 11 (2nd November 2019) - Jin, Xin; Xiang, Yang; Weber, Karin; Liu, Yang
ABSTRACT: This research aims to explore Chinese tourists' motivations and involvement in adventure tourism activities, as well as if and how personality and location affect their motivation and involvement. Using a survey that collected 252 responses, this research suggests that stimulus-avoidance and intelligence seeking are the two most important motivational forces. Results indicate that respondents would prefer overseas locations for these activities due to perceptions of greater safety and security, better service, and higher-quality facilities. Respondents who rated themselves as "open" or "closed" in personality differ regarding motivations and involvement. Practical implications are discussed, and recommendations for future research are provided.